High-grade Müllerian Adenosarcoma: Genomic and Clinicopathologic Characterization of a Distinct Neoplasm With Prevalent TP53 Pathway Alterations and Aggressive Behavior. (November 2017) - Hodgson, Anjelica; Amemiya, Yutaka; Seth, Arun; Djordjevic, Bojana; Parra-Herran, Carlos
Abstract : Müllerian adenosarcoma harbors low malignant potential, except in cases with myometrial invasion or sarcomatous overgrowth. The presence of a high-grade stromal component has been proposed as an important pathologic predictor of outcome. We hypothesized that high-grade adenosarcoma has distinct clinical and molecular features, distinct from low-grade adenosarcoma. We analyzed the clinicopathologic features and follow-up of 9 high-grade adenosarcomas and a control group of 9 low-grade adenosarcomas. Comprehensive genomic analysis of the high-grade group was performed targeting exons of 409 oncogenes and tumor suppressor genes. In 1 case, the high-grade and low-grade components were separately sequenced. High-grade and low-grade adenosarcomas were comparable in patient age, myometrial invasion, and stage at presentation. Sarcomatous overgrowth was observed in 2/9 (22%) low-grade and 8/9 (89%) high-grade adenosarcomas. Six of 9 (67%) patients with high-grade adenosarcoma developed rapid recurrence; 1 died of her disease. Conversely, no low-grade tumors recurred or metastasized. Sequencing of high-grade adenosarcomas revealed frequent TP53 pathway alterations, identified in 7/9 (78%) cases. p53 expression by immunohistochemistry highly correlated with mutation status. Copy number variations occurred at a mean of 28.8 per tumor; most frequently involved genes included CDK4, MDM2, GNAS, SGK1, and DICER1 . High-grade adenosarcoma is an aggressive neoplasm with propensity for short-interval recurrence and metastasis. The proportion of copy number alterations is similar to that reported for adenosarcoma with sarcomatous overgrowth. However, the high frequency of TP53 abnormalities is a novel finding, indicating that high-grade adenosarcoma is a distinct subset with driver TP53 pathway alterations. p53 immunohistochemistry can be used to confirm the presence of a high-grade component. Given its aggressive potential, the presence of any high-grade component in an adenosarcoma should be reported, even in the absence of sarcomatous overgrowth.